A study of pre-school children's school readiness related to scientific thinking skills - (:unkn) unknown (My University, 2006)
The purpose of this study is to compare school readiness of children who had pre-school experiences and children without such experiences on the basis of scientific thinking skills. This comparison is held in terms of variables of age, gender, and socio economic status. The questions of the study in relation to the purpose of the study are as follows: ▷ Does pre-school education variable influence primary school readiness of pre-school children in terms of scientific thinking skills? ▷ Does age variable influence primary school readiness of pre-school children in terms of scientific thinking skills? ▷ Does gender variable influence primary school readiness of pre-school children in terms of scientific thinking skills? ▷ Does socio-economical status variable influence primary school readiness of pre-school children in terms of scientific thinking skills?
Keywords: Pre-school; Problem solving; Readiness; Scientific thinking